The Acari Hypothesis, VII: accounting for the comorbidity of allergy with other contemporary medical conditions, especially metabolic syndrome - Andrew C. Retzinger; Gregory S. Retzinger (Frontiers in Allergy)
The Acari Hypothesis proposes that vector-active acarians, i.e., mites and ticks, are the etiologic agents responsible for most, if not all, allergies. A corollary of The Hypothesis posits allergies are now more prevalent because contemporary hygienic practices remove from skin elements of sweat that otherwise deter acarians. Because the antimicrobial activity of sweat extends beyond acarians, disruption/removal of sweat on/from skin must enable aberrant microbial colonization, possibly potentiating comorbid conditions assignable to the aberrant microbial colonist(s). Allergy is strongly comorbid with metabolic syndrome. Available evidence links the principal features of metabolic syndrome to Staphylococcus aureus, an organism influenced significantly by constituents of sweat. Thus, the removal of sweat predisposes to both allergy and metabolic syndrome. Indeed, the “immune-compromised” state brought upon by contemporary hygienic practices likely accounts for the comorbidity of many contemporary medical conditions, examples of which are highlighted.